Respuesta :

Answer:

a = 3 ,  b = -2 ,  c = 0

Step-by-step explanation:

The given equation is:

1 = -2x + 3x^2 + 1

To find the correct substitution values of a, b and c. We need to convert t into the standard form first.

Standard form of a Quadratic equation is written as:

ax^2 + bx + c = 0        (where a is not equal to zero)

Converting the given equation into its standard form:

1 = -2x + 3x^2 + 1

-2x + 3x^2 + 1 - 1 = 0

3x^2 - 2x + 0 = 0  

OR 3x^2 - 2x = 0

According to the equation

a = 3 ,  b = -2 ,  c = 0

ACCESS MORE